Argumentasi Hukum Penuntut Umum Menyusun Dakwaan Tunggal Dalam Perkara Pencurian Dengan Kekerasan - Surya Guritno (Verstek, 2017)
Purpose of research to the public prosecutor's argument arrange single indictment in the case of theft with violence resulting in death where Justice in its advisory opinion against the defendants acquitted in the case number: 817 / Pid.B / 2013 / PN.Smg.    The criminal act of theft had occurred on Sunday, October 27, 2013 approximately at 03.30.wib at Jl. Dr. Wahidin Semarang. Defendant I and Defendant II rob her purse and pushed fall off her motorbike death as a result.    The crime of theft with violence that law argumentations of public prosecutor compile singular conformity with Criminal Procedure Code (KUHAP), in this case the Prosecutor General shall establish the charges under Article 143 paragraph (2) Criminal Procedure Code. On the other hand is based on a system of verifying negative verdict Judge-free for non-fulfillment of the minimum threshold of proof as provided for in Article 191 paragraph (1) Criminal Code, the judge is legally inappropriate and unreasonable to acquit the defendants of all charges and demands of the public prosecutor.     Keywords: Law Argumentations, Indictment, The Judge Considerations.